2023
DOI: 10.1007/s40120-023-00445-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing What Matters to People Affected by Alzheimer’s Disease: A Quantitative Analysis

Abstract: Introduction:In this phase of the ongoing What Matters Most study series, designed to evaluate concepts that are meaningful to people affected by Alzheimer's disease (AD), we quantified the importance of symptoms, impacts, and outcomes of AD to people at risk for or with AD and care partners of people with AD. Methods: We administered a web-based survey to individuals at risk for or with AD (Group 1: unimpaired cognition with evidence of AD pathology; Group 2: AD risk factors and subjective cognitive complaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…During the second phase of WMM, 274 people identified by clinicians as living with or at risk for AD, or those with self-reported confirmed genetic risk profile, and their care partners completed an online survey to rate the importance, on a scale of 1-5, of the 42 treatment-related outcomes identified in phase 1, thereby further supporting and confirming the qualitative findings [2]. This quantitative evaluation confirmed that all WMM items were at least moderately important to all patient groups (minimum importance rating, 3.4; maximum rating, 4.6), and most were at least moderately important to both care partner groups (minimum importance rating, 2.1; maximum rating, 4.4).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…During the second phase of WMM, 274 people identified by clinicians as living with or at risk for AD, or those with self-reported confirmed genetic risk profile, and their care partners completed an online survey to rate the importance, on a scale of 1-5, of the 42 treatment-related outcomes identified in phase 1, thereby further supporting and confirming the qualitative findings [2]. This quantitative evaluation confirmed that all WMM items were at least moderately important to all patient groups (minimum importance rating, 3.4; maximum rating, 4.6), and most were at least moderately important to both care partner groups (minimum importance rating, 2.1; maximum rating, 4.4).…”
Section: Introductionmentioning
confidence: 63%
“…In phase 1 of WMM, we conducted qualitative research with individuals at risk for or living with mild AD and care partners of individuals with more advanced AD to identify a comprehensive set of 42 AD symptoms, impacts, and treatment-related outcomes that are meaningful to individuals across the AD continuum [1]. Building on this qualitative study, Hauber et al [2] evaluated the concepts that are meaningful to people affected by AD and quantified the importance of symptoms, impacts, and outcomes of AD to people at risk for or with AD and care partners of people with AD. As a third stage in this integrated and iterative research process, this study examined the relationship between concepts of importance identified by patients and care partners in the What Matters Most study series [2] and concepts assessed in frequently used COAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations